2017
DOI: 10.1007/s10456-017-9571-8
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in multiple myeloma neovascularization: a brick to the wall

Abstract: Multiple myeloma (MM) is characterized by the clonal expansion of plasma cells in the bone marrow that leads to events such as bone destruction, anaemia and renal failure. Despite the several therapeutic options available, there is still no effective cure, and the standard survival is up to 4 years. The evolution from the asymptomatic stage of monoclonal gammopathy of undetermined significance to MM and the progression of the disease itself are related to cellular and molecular alterations in the bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 170 publications
1
26
0
Order By: Relevance
“…The expression of CD133 on a subset of BM endothelial cells during the active phase of the disease is indicative of the recruitment of CD133+ progenitor cells, derived from a common progenitor namely hemangioblast, which contributes to the neovascularization by means of the reactivation of the ancestral phenomenon named "vasculogenesis" [23][24][25][26][27].…”
Section: The "Vascular Niche"mentioning
confidence: 99%
“…The expression of CD133 on a subset of BM endothelial cells during the active phase of the disease is indicative of the recruitment of CD133+ progenitor cells, derived from a common progenitor namely hemangioblast, which contributes to the neovascularization by means of the reactivation of the ancestral phenomenon named "vasculogenesis" [23][24][25][26][27].…”
Section: The "Vascular Niche"mentioning
confidence: 99%
“…It enhances vascular permeability, facilitates plasma extravasation, increases interstitial pressure, induces hypoxia, and upregulates hypoxia-inducible factor-1 alpha (HIF-1α) and VEGF [39]. Some MM endothelial cells express the CD133 indicating their derivation from a subset of CD133+ progenitor cells which contribute to the formation of blood neovessels [26,40,41]. MM plasma cells recruit BM and circulating CD133+ progenitor cells into the tumor microenvironment by mean the release of a high quantity of VEGF, FGF-2, and IGF [26].…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Various studies have demonstrated that endothelial progenitor cells (EPCs) can be isolated from patients with MM [40,[66][67][68][69] and contribute to the formation of new blood vessels [40]. Moreover, circulating EPCs expressing CD146+, CD105+, and CD34+ are increased in MM patients compared to healthy controls [66,67].…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…Under high glucose condition associated with ECs dysfunction, decreasing miR-126 could increase SDF-1 expression, and also directly increased progenitor cells migration and adhesion [11,12] , and further improve stroke outcome by differentiating into endothelial cells or through the paracrine effects. Tenreiro et al [13] demonstrated endothelial cells improved ischemic recovery by differentiation into ECs. Chen et al [14] demonstrated progenitor cells secreted IL-8 to promote angiogenesis during ischemia.…”
Section: Mir-126 Promotes Angiogenesis After Ischemic Strokementioning
confidence: 99%